Efficacy and Safety of a Novel Adsorber for LPS-Selective Hemosorption (Experimental Study) - Sergey E. Khoroshilov; Artem V. Nikulin; Ivan V. Bessonov; Alexander S. Morozov; Ivan V. Yarema (Общая реаниматология, 2018)
The purpose of the study is to evaluate the in vitro and ex vivo effectiveness and safety of a new device for extracorporeal blood purification.Materials and methods. The sorption properties and safety of hemoperfusion using the LPS sorption column that employs hypercrosslinked styrene-divinylbenzene copolymer.were studied using three different models:1) Escherichia coli endotoxin solution in aqueous 0.9% NaCl solution with an assessment of the efficacy of endotoxin elimination,2) donor erythrocyte suspension with assessment of the hemoperfusion column safety for blood cells,3) whole donor blood with assessment of hemosorption efficacy and hemoperfusion safety of the new column. Results. There was a 18.5-fold decrease in the endotoxin concentration in 0.9% sodium chloride solution over2 hours of perfusion vs. the baseline, while maintaining the residual sorption capacity of the column. Perfusion of RBC suspension and freshly prepared donor blood through the new LPS column did not demonstrate the emergence and growth of cytolytic markers; on the contrary, a two-fold decrease in the concentration of free hemoglobin containing in the RBC suspension was observed. There was a two-fold decrease in the vitamin B12 concentration, a 3.54-fold decrease in β2-microglobulin and a 2.5-fold decrease in creatinine levels. The atomic force microscopy did not find critical impairment of the morphology of erythrocyte membranes.Conclusion. In vitro and ex vivo tests demonstrated reliable experimental data on the effectiveness and safety of the device that employs a hypercrosslinked styrene-divinylbenzene copolymer for LPS-selective hemosorption, which was not inferior to one of analogues for hemosorption currently employed in clinical practice.